2009
DOI: 10.1109/tcomm.2009.07.070525
|View full text |Cite
|
Sign up to set email alerts
|

Turbo receivers for interleave-division multiple-access systems

Abstract: In this paper several turbo receivers for Interleave-Division Multiple-Access (IDMA) systems will be discussed. The multiple access system model is presented first. The optimal, Maximum A Posteriori (MAP) algorithm, is then presented. It will be shown that the use of a precoding technique at the emitter side is applicable to IDMA systems. Several low complexity Multi-User Detector (MUD), based on the Gaussian approximation, will be next discussed. It will be shown that the MUD with Probabilistic Data Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We note that some part of the equivalence shown above for IDMA systems have been discussed in the literature for BPSK in [29], [38], [39] whereas our proof is more general for complex modulation alphabets = { 1 , . .…”
Section: (For Idma Under Assumption Iii2)mentioning
confidence: 77%
See 1 more Smart Citation
“…We note that some part of the equivalence shown above for IDMA systems have been discussed in the literature for BPSK in [29], [38], [39] whereas our proof is more general for complex modulation alphabets = { 1 , . .…”
Section: (For Idma Under Assumption Iii2)mentioning
confidence: 77%
“…We analyze the system using EXIT chart [21], [24], [38], [48], which is a convenient tool for studying iterative processing techniques. The EXIT chart shows the average mutual information between the transmitted code bits and the input LLRs, which are obtained from the other soft-in soft-out block, versus the average mutual information between the transmitted code bits and the extrinsic output LLRs, which are sent to the other block.…”
Section: Analysis Using Extrinsic Information Transfer Chartsmentioning
confidence: 99%
“…The proposed technique in [3] is in contrast to the code-division multiple access (CDMA), where users are separated through user-specific spreading sequences [4]. In comparison with CDMA, the IDMA has significant advantages such as less complex detection scheme without compromising the diversity gain [5,[6][7][8][9]. Further the IDMA outperforms the CDMA when it is integrated with iterative turbo decoding schemes at the receiver terminal [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with CDMA, the IDMA has significant advantages such as less complex detection scheme without compromising the diversity gain [5,[6][7][8][9]. Further the IDMA outperforms the CDMA when it is integrated with iterative turbo decoding schemes at the receiver terminal [4,5,8]. The other important significance of the IDMA is the easy integration with MIMO systems [10].…”
Section: Introductionmentioning
confidence: 99%
“…This includes the usage of low complex multiuser detectors than required for CDMA systems [5]- [12]. Further studies in [4] [5] [13]- [18] have proven that IDMA systems can outperform CDMA when iterative (turbo) receivers are used. Therefore recent developments have shown that IDMAs can be easily integrated into the MIMO systems [15].…”
Section: Introductionmentioning
confidence: 99%